2015
DOI: 10.1071/ma15063
|View full text |Cite
|
Sign up to set email alerts
|

An effective and feasible approach to prevention of primary cytomegalovirus infection in pregnancy

Abstract: In the absence of a cytomegalovirus (CMV) vaccine, other strategies for prevention of primary infection in pregnancy should be considered. Behavioural interventions have been reported to significantly decrease seroconversion rate among seronegative pregnant women. We report here on a recently completed controlled study in which seronegative women at high risk of infection because of close contacts with children <36 months, were identified and informed about risky and protective behaviours. Informed women seroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Since there is no effective vaccine against the cCMV infection yet, simple hygienic precautions remain the only successful strategy to prevent of cCMV infection. The rate of vertical transmission of CMV infection from mother to fetus is dependent on the time of mother’s infection [ 8 10 ]. Previous studies suggest that there is a limited awareness or knowledge about cCMV and prevention strategies among women who have educated by Family Practice Physicians and also it has been shown that delivery of prevention counseling to the pregnant women by healthcare providers were highly effective at raising awareness among pregnant women [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no effective vaccine against the cCMV infection yet, simple hygienic precautions remain the only successful strategy to prevent of cCMV infection. The rate of vertical transmission of CMV infection from mother to fetus is dependent on the time of mother’s infection [ 8 10 ]. Previous studies suggest that there is a limited awareness or knowledge about cCMV and prevention strategies among women who have educated by Family Practice Physicians and also it has been shown that delivery of prevention counseling to the pregnant women by healthcare providers were highly effective at raising awareness among pregnant women [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%